Economic Valuation of Mangrove Forest in The East Coast of The City Of Surabaya, East Java Province, Indonesia - Kusumawardani, Deni (Journal of Developing Economies, 2019)
The city of Surabaya has been voted as one of the pilot areas of mangrove forest conservation in ASEAN. Most of the mangrove forest area in the city of Surabaya spread across the East Coast (Pamurbaya). The purpose of this study is to estimate the total economic value of mangrove forests in the area as a source of information for planning and evaluation of conservation policy. The results of the valuation involving some valuation techiques, both market and non-market approaches, yield total economic value of about Rp 49.6 billion (US$ 3.8 million) per year, or 105.3 million (US$ 8,101.8) per ha per year. Almost all of these values is the use value, particularly direct use valule both extractive (timber and fisheries) and non extractive (outdoor recreation). Indirect use value which consists of abrasion barrier and carbon sinks contributed relatively small compared to the direct use value. Meanwhile, non-use value is the smallest contributors to the total economic value. This fact proves that the mangrove forest in Pamurbaya has economic benefits outweigh the ecological benefits. Keywords: Economic Valuation, Mangrove, Non-Market Approach, The Cityof SurabayaJEL Classification: A130, D78